2017
DOI: 10.1111/tbj.12810
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effectiveness of the prepectoral breast reconstruction with Braxon dermal matrix: First multicenter European report on 100 cases

Abstract: We report the outcomes of the European prospective study on prepectoral breast reconstruction using preshaped acellular dermal matrix for complete breast implant coverage. Seventy-nine patients were enrolled between April 2014 and August 2015 all over Europe using a single protocol for patient selection and surgical procedure, according to the Association of Breast Surgery and British Association of Plastic Reconstructive and Aesthetic Surgeons joint guidelines for the use of acellular dermal matrix in breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 28 publications
(72 reference statements)
7
75
1
4
Order By: Relevance
“…In the prepectoral technique, operating time is reduced as it is a less complicated technique and the surgeon can begin to perform the ex vivo procedure of suturing the Braxon ® mesh (Figure 1) around the implant after the mastectomy, while haemostasis and irrigation of the prepectoral space are being carried out. Berna et al did not report any implant loss in their small series of 15 implant-based IBR using Braxon ® and Vidya et al in a series of 100 cases has demonstrated a very low implant loss rate of 2% (18,19). However, our complication rate of wound infection and implant loss were comparable to the NMBRA results which reported on subpectoral implant based reconstruction ( Table 3) (10).…”
Section: Discussioncontrasting
confidence: 47%
“…In the prepectoral technique, operating time is reduced as it is a less complicated technique and the surgeon can begin to perform the ex vivo procedure of suturing the Braxon ® mesh (Figure 1) around the implant after the mastectomy, while haemostasis and irrigation of the prepectoral space are being carried out. Berna et al did not report any implant loss in their small series of 15 implant-based IBR using Braxon ® and Vidya et al in a series of 100 cases has demonstrated a very low implant loss rate of 2% (18,19). However, our complication rate of wound infection and implant loss were comparable to the NMBRA results which reported on subpectoral implant based reconstruction ( Table 3) (10).…”
Section: Discussioncontrasting
confidence: 47%
“…Recently, the long-term results of clinical studies on the pre-pectoral reconstructions by means of a synthetic matrix were published (11,12). Several other studies reported similar results with biological matrixes (8,(13)(14)(15)(16)(17)(18)(19). A pre-pectoral approach showed, in all these series, a highly documented surgical safety, comparable to the standard full muscular coverage and to the dual-plane coverage.…”
Section: Surgical Techniquesupporting
confidence: 54%
“…The past decade has seen a steady rise in implant and expander-based immediate breast reconstruction, from about 30 per cent in 2007 to 54 per cent in 2013 3 . Two recent multicentre European studies 13,18 reported acceptable operative outcomes, comparable to subpectoral reconstruction. Subpectoral implant placement has been the conventional method, with complete coverage of the implant using pectoralis major muscle above and acellular dermal matrix (ADM) in the lower and outer aspect.…”
Section: Introductionmentioning
confidence: 93%